2019
DOI: 10.1093/labmed/lmz003
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100A8/A9 as a Potentially Sensitive Biomarker for Inflammatory Bowel Disease

Abstract: Background The clinical significance of human S100A8/A9 (h-S100A8/A9) in patients with inflammatory bowel disease (IBD) is poorly understood. Objective To clarify whether serum S100A8/A9 is a sensitive biomarker for IBD. Methods Serum specimens from outpatients with IBD (n = 101) and healthy volunteers (HVs) (n = 101) were used in this study. Enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
3
23
1
Order By: Relevance
“…Hence, CXCR2 is a potential target for UC treatment (Zhu et al, 2020). LCN2 (Østvik et al, 2013;Stallhofer et al, 2015;Buisson et al, 2018;Zollner et al, 2021) and S100A8 (Manolakis et al, 2011;Azramezani Kopi et al, 2019;Okada et al, 2019Okada et al, , 2020 are critical proinflammatory cytokines that have been reported in recent studies as potential molecular markers of UC in serum and stool samples. LCN2 and S100A8 also have antimicrobial effects and may be involved in the regulation of intestinal flora as antimicrobial peptides, which may be indirectly related to UC.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, CXCR2 is a potential target for UC treatment (Zhu et al, 2020). LCN2 (Østvik et al, 2013;Stallhofer et al, 2015;Buisson et al, 2018;Zollner et al, 2021) and S100A8 (Manolakis et al, 2011;Azramezani Kopi et al, 2019;Okada et al, 2019Okada et al, , 2020 are critical proinflammatory cytokines that have been reported in recent studies as potential molecular markers of UC in serum and stool samples. LCN2 and S100A8 also have antimicrobial effects and may be involved in the regulation of intestinal flora as antimicrobial peptides, which may be indirectly related to UC.…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher receptor for advanced glycation end products (RAGE). Therefore, S100A8 and S100A9 are essential causative stimulators in inflammatory diseases, and may be used as biomarkers and therapeutic targets [5][6][7].…”
Section: Ivyspringmentioning
confidence: 99%
“…In GOBP analysis, these gene families were involved in the development of cytokine-mediated signaling pathway, leukocyte migration, and myeloid leukocyte activation, and the results were similar to the KEGG analysis. Genes such as DOUX2 (Haberman et al, 2014), S100A8/A9 (Okada et al, 2019), CHI3L1 (Deutschmann et al, 2019), TNFRSF6B (Eriksson et al, 2008), and SLC6A14 (Luther et al, 2018) are also associated with CD. Although the colonic and terminal ileal tissues share a similar inflammatory status in CD, they may have different transcriptomes due to different genetic microenvironments and microbiomes.…”
Section: Discussionmentioning
confidence: 99%